2008
DOI: 10.1007/s11270-008-9773-1
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Uncertainty in a Pre-treatment Dataset when Estimating Treatment Effects in Paired Catchment Studies: Phosphorus Loads from Forest Clear-cuts

Abstract: Estimates of increased nutrient export caused by forest clear-cuttings are mostly based on long-term paired catchment studies, where the treatment effect is calculated using pre-treatment dataset regression and post-treatment records of nutrient loads. In these studies uncertainty in the regression between the pre-treatment loads from the control and from the treatment catchments is typically neglected, even though it affects determination of the magnitude and duration of the treatment effect. This uncertainty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…There is also uncertainty in the relationship between the treatment and control catchments during the pre-treatment period. Unlike many other studies, we took into account the uncertainty in the regression between the pre-treatment concentrations from the control and the treatment catchments and avoided the overinterpretation of the results (Laurén et al 2009). The number of existing studies is small considering large site-specific variation in responses to clear-cutting but produced specific concentration values cannot be improved without new data.…”
Section: Reliability Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also uncertainty in the relationship between the treatment and control catchments during the pre-treatment period. Unlike many other studies, we took into account the uncertainty in the regression between the pre-treatment concentrations from the control and the treatment catchments and avoided the overinterpretation of the results (Laurén et al 2009). The number of existing studies is small considering large site-specific variation in responses to clear-cutting but produced specific concentration values cannot be improved without new data.…”
Section: Reliability Of Resultsmentioning
confidence: 99%
“…The concentrations for the treatment catchments as if they had not been treated are calculated as f j (a j C ij f j -1 ). This approach is based on the work by Laurén et al (2009) and Nieminen et al (2010) and further information can be found therein. The advantage of this approach, as compared to more conventional methods is that the random variability between treatment and control catchments during the calibration period and the proportional size of the treated area can be taken into account in the interpretation of the treatment effects.…”
Section: Calculations and Statistical Analysesmentioning
confidence: 99%
“…Some P reaches the stream, especially outside the growing season when the biological activity is low (Väänänen et al 2006). An uncut forested buffer between the clear cut area and the receiving surface water is found to be effective in mitigating P leaching from clear cuts (Niemelä 2001;Laurén et al 2009) (Box 1; Fig. 2).…”
Section: Buffering Impacts From Clear Cutsmentioning
confidence: 99%
“…During the first 3 years after cutting, the increase without buffer was 1.4 kg ha -1 year -1 of catchment area. Background leaching was 0.1-0.2 kg ha -1 year -1 (modified from Laurén et al 2009) Box 1 An intact RF buffer zone reduced suspended solids and nutrient export to water bodies after forest clear cutting in Finland…”
Section: Managing Buffer Zones For Water Protectionmentioning
confidence: 99%
See 1 more Smart Citation